Macrophagic myofasciitis: a challenging diagnosis. (3rd July 2018) - Soares Santos, Daniela; Santos, Arsénio; Rebelo, Olinda; Santos, Rui M
Abstract : A 25-year-old man admitted for generalised muscle pain with an insidious onset 3 years ago. He had exercise intolerance and decrease in muscle strength, requiring gait support. He was previously healthy, with no chronic medication or recent history of drugs or toxics. National vaccination plan actualised with hepatitis B and tetanus vaccines administered 10 and 2 years, respectively, before symptom onset. No analytical, imaging or electromyography changes were found. Muscle biopsy revealed an inflammatory infiltrate predominantly macrophagic with aluminium deposits suggestive of macrophagic myofasciitis (MMF). It is probably associated with vaccines previously administered. MMF lesion can be regarded as pathological only if detected at least 18 months after last aluminic immunisation, as our case illustrates.